A Role for the Transcription Factor Arid3a in Mouse B2 Lymphocyte Expansion and Peritoneal B1a Generation - Habir, Katrin; Aeinehband, Shahin; Wermeling, Fredrik; Malin, Stephen (Frontiers in Immunology, 2017)
The initiation, commitment and terminal differentiation of the B cell lineage is stringently controlled by the coordinated action of various transcription factors. Among these, Arid3a has previously been implicated in regulating early B lymphopoiesis, humoral immune responses to phosphocholine and furthermore to promote the B1 over the B2 cell lineage. We have now interrogated the function of Arid3a in the adult mouse using conditional mutagenesis. We demonstrate that loss of Arid3a does not affect early B cell development or lineage commitment but rather loss of this transcription factor results in a broad expansion of bone marrow B lymphopoiesis in a manner that reflects its developmental expression pattern. Furthermore, loss of Arid3a resulted in expanded splenic B cell numbers with the exception of the B1 lineage which maintained at normal numbers. However, B1a lymphoyctes were reduced in the peritoneal cavity. Additionally, antibody responses to phosphocholine were attenuated in the absence of Arid3a. Hence, functional Arid3a is required in mature B cells for specific immune responses and for generating normal numbers of B cells in a subset dependent manner.